UJI DAYA KECAMBAH DAN UJI DAYA TUMBUH BENIH BEBERAPA TANAMAN PANGAN: SUATU PENDEKATAN UNTUK HASIL BERKELANJUTAN: SEEDS VIABILITY AND VIGOR TEST OF SEVERAL FOOD CROPS: AN APPROACH TOWARDS SUSTAINABLE YIELD - SYARANAMUAL, SISKA; MUYAN, YAVED; SARUNGALLO, AMELIA SAMMIN (Fakultas Pertanian Universitas Palangka Raya, 2024)
The study aims to determine the quality of food crop seeds accessed by farmers in Manokwari Regency. It was conducted at the Agroclimatology Laboratory, Faculty of Agriculture, The University of Papua, by applying the viability and vigor tests on five selected seeds, namely corn, peanut, long bean, mung bean and kangkong (Ipomoea) seeds on straw paper and sand media. The results showed that the tested food plant seeds were categorized as good based on predetermined standards. Corn seeds showed the highest germination test, while the lowest was produced by kangkong seeds. Mung bean seeds recorded the highest growth speed compared to other seeds. At the vigor test, peanut seeds performed better results than other seeds while kangkong seeds consistently recorded the lowest yields. This study recommends future work in terms of seed tests with certain treatments along with different types of seeds.